PENGARUH EKUITAS MERK DAN LINGKUNGAN SOSIAL TERHADAP NIAT BELI KONSUMEN PADA PRODUK GIORDANO - Prabawa Putra, Putu Mona; Mandala, Kastawan (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p11, 2018)
The research paper aims to leverage the influence of brand equity and social environment on consumer buying intentions on Giordano products in Denpasar City. This scientific work is done in Denpasar City with multiple linear regression analysis technique. The sample size is 120 respondents by using purposive sampling method . The results of the analysis can be stated that brand equity directly affects positively to consumer purchase intentions on clothing products Giordano in the city of Denpasar. The social environment directly positively affects consumers' purchase intentions on Giordano clothing products in Denpasar City. Recommended suggestions for Giordano should clearly illustrate Giordano brand products in the eyes of consumers so that consumers are able to recognize Giordano brand products and are interested in making purchases. Provides information about Giordano's products better and more detail to the consumer so that it can be promoted to his family, his neighbors in adding references in making a purchase.